PERAN PEMERINTAH INDONESIA DALAM MENDORONG TRANSISI ENERGI MELALUI SOUTH-SOUTH AND TRIANGULAR COOPERATION - Wijanarka, Tunjung; Dewi, Ni Nyoman Clara Listya (Indonesian Association for International Relations, 2024)
This article examines the Indonesian government’s role in using the South-South and Triangular Cooperation (SSTC) mechanism to promote clean energy transition and accomplish the Paris Agreement’s Nationally Determined Contribution (NDCs) targets through the Clean, Affordable, and Secure Energy for Southeast Asia (CASE) Project. The SSTC is a multi-sector cooperation framework among states that includes governmental actors, international organizations, and civil society, with the goal of pursuing sustainable development. This research employs Green theory and SSTC norms through a qualitative descriptive analysis and data gathering methods based on a literature review. The study indicates that the CASE Project, through collaborative initiatives involving grassroots movements, can evantually support the Indonesian government in attaining renewable energy transition and national NDC targets.